Comparison of High-Protein, Intermittent Fasting Low-Calorie Diet and Heart Healthy Diet for Vascular Health of the Obese - Zuo, Li; He, Feng; Tinsley, Grant M.; Pannell, Benjamin K.; Ward, Emery; Arciero, Paul J. (Frontiers in Physiology, 2016)
Aim: It has been debated whether different diets are more or less effective in long-term weight loss success and cardiovascular diseases among men and women. Thus, the present study evaluated the combined effects of a high-protein, intermittent-fasting, low-calorie diet plan compared with heart healthy diet plan during weight loss maintenance on blood lipids and vascular compliance of individuals with obesity. Methods: The experiment involved 40 adults with obesity (men, n = 21; women, n = 19) and was divided into two phases: (a) 12-week high-protein, intermittent-fasting, low-calorie weight loss diet comparing men and women (Phase 1) and (b) a 1-year (52-week) weight loss maintenance comparing high-protein, intermittent-fasting with a heart healthy diet (Phase 2). Body weight, body mass index, blood lipids, and arterial compliance outcomes were assessed at weeks 1 (baseline control), 12 (weight loss), and 64 (12+52 week; weight loss maintenance). Results: At the end of weight loss intervention, concomitant with reductions in body weight, body mass index, blood lipids, and arterial compliance was enhanced (p < 0.05). No sex-specific differences were observed. During phase 2, high-protein, intermittent-fasting, low-calorie group demonstrated less weight regain and percentage change in aortic pulse wave velocity than heart healthy group (p < 0.05). Conclusion: Our results suggest that high-protein, intermittent-fasting and low-calorie diet is associated with body weight loss and reduction in blood lipids. This diet also demonstrated a potential advantage in minimizing weight gain relapse as well as enhancing arterial compliance compared to the heart healthy diet in the long term.